From anecdotes to scientific evidence? A review of recent literature on catch share systems in marine fisheries. Issue 8 (18th September 2012) - Thébaud, Olivier; Innes, James; Ellis, Nick
Abstract : In response to concerns regarding the global status of living marine resources, there has been a worldwide tightening of fishery access regulations. This has led to growing interest in individual transferable catch share programs, a market‐based allocation approach to distribute fishing rights. However, the economic, ecological, and social benefits of these systems are the subject of continued debate. Here, we review empirical studies of transferable catch share systems published over the past decade. Our results show that, despite some of these systems having been in place for more than 20 years, systematic empirical assessments of their impacts are still rare. Furthermore, methods used to assess the impacts of catch share systems to facilitate comparisons remain under development, making it difficult to derive general conclusions from existing studies.